(untitled) (Sahel Journal of Life Sciences FUDMA, 2024)
In recent decades, medicinal plants have been of great interest as they have been the sources of natural products. As a result, there is a need to analyse the phytochemical and antibacterial properties of Eucalyptus globulus against Escherichia coli, Bacillus cereus, Staphylococcus aureus and Pseudomonas aeruginosa. This study was carried out to determine the percentage yield, phytochemical properties, antibacterial activity, minimum inhibitory and minimum bactericidal concentration (MIC/MBC) of the crude extracts using the reflux extraction, qualitative phytochemical, agar well diffusion and broth dilution method respectively; while aqueous, normal hexane and ethyl acetate were used as extraction solvents. Aqueous extract has the highest yield of 16.08%, ethyl acetate extract (8.76%) while n-hexane extract had 3.84%. Phytochemicals such as tannins, alkaloids, and phenols were present in all three solvent extracts; while terpenoids, glycosides and steroids were absent. Saponins and flavonoids were present in water extract, flavonoids were present only in the ethyl acetate extract. The most active with mean inhibition zone (MIZ) diameter of 13.33±0.58mm and 10.33±0.58mm against Bacillus cereus and Staphylococcus aureus respectively at 50mg/mL while the lowest activity of MIZ diameter of 8.00±2.00mm was obtained with same extract and concentration against Escherichia coli. N-hexane and ethyl acetate extracts show no activity against the test organisms. The lowest MIC of 15.6mg/mL and MBC of 31.3mg/mL were obtained against Escherichia coli. Based on these results, it can be concluded that Eucalyptus globulus leaf extracts possess antibacterial activity against some of the test organisms and can be considered for drug development.